2017
DOI: 10.4143/crt.2016.326
|View full text |Cite
|
Sign up to set email alerts
|

CA19-9 or CEA Decline after the First Cycle of Treatment Predicts Survival in Advanced Biliary Tract Cancer Patients Treated with S-1 and Cisplatin Chemotherapy

Abstract: PurposeWhile tumor markers (carbohydrate antigen 19-9 [CA 19-9] and carcinoembryonic antigen [CEA]) can aid in the diagnosis of biliary tract cancer, their prognostic role has not been clearly elucidated. Therefore, this study was conducted to evaluate the prognostic role of tumor markers and tumor marker change in patients with advanced biliary tract cancer.Materials and MethodsPatients with pathologically proven metastatic or relapsed biliary tract cancer who were treated in a phase II trial of first-line S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Likewise, Park et al [23] recently reported that CEA independently predicts prognosis in patients with metastatic BTC. Consistent with previous studies [23, 24], the results of our study demonstrated that baseline CA 19–9 and CEA level were independent prognostic markers.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, Park et al [23] recently reported that CEA independently predicts prognosis in patients with metastatic BTC. Consistent with previous studies [23, 24], the results of our study demonstrated that baseline CA 19–9 and CEA level were independent prognostic markers.…”
Section: Discussionsupporting
confidence: 93%
“…Another recent study with patients suffering from advanced and inoperable bile duct cancers (212 patients in the investigational cohort and 677 patients in tree independent validation cohorts) showed that the decline of CA 19-9 serum level during chemotherapy was predictive for longer OS (HR=0.60, 95%CI=0.44-0.80, p<0.0005) (16). Similarly, the decline of CA19-9 and CEA ≥30% after the first cycle of S-1 and cisplatin chemotherapy in 104 patients with metastatic or relapsed biliary tract cancers served as a positive prognostic factor of time to progression (HR=0.44, p=0.003) as well as OS (HR=0.37, p<0.001) in the multivariate analysis (17). In another recent study with biliary tract cancer patients undergoing resection with curative intent, the worse 3-year OS was observed among patients with an abnormally high (≥37 U/ml) preoperative as well as postoperative CA19-9 levels by comparison with those with either the high preoperative and normal postoperative CA19-9 levels, or normal preoperative CA19-9 level (3-year OS rate 31, 73, and 70.4% respectively, p<0.001) (18).…”
Section: Discussionmentioning
confidence: 86%
“…In a study of 26 patients with advanced gastric cancer and with elevation of at least one of the three tumor makers (CEA, CA 19.9, CA 125) before starting systemic chemotherapy, the authors demonstrated a significant difference in survival amongst responders (assessed by drop in tumor markers levels) as compared to non-responders (p = 0.0056) [22]. Similarly, Lee et al demonstrated that the decrease in the tumor marker level after chemotherapy was associated with improved survival in advanced biliary tract cancer patients [23]. They reported tumor marker decline as an independent positive prognostic factor for improved time to progression (TTP) (adjusted HR 0.44; p = 0.03) and overall survival (adjusted HR 0.37; p = 0.001) in these patients after the first cycle of chemotherapy [23].…”
Section: Tumor Marker Correlationmentioning
confidence: 90%
“…Similarly, Lee et al demonstrated that the decrease in the tumor marker level after chemotherapy was associated with improved survival in advanced biliary tract cancer patients [23]. They reported tumor marker decline as an independent positive prognostic factor for improved time to progression (TTP) (adjusted HR 0.44; p = 0.03) and overall survival (adjusted HR 0.37; p = 0.001) in these patients after the first cycle of chemotherapy [23]. In our study, we were able to demonstrate an absolute decline in CEA levels after treatment with neoadjuvant IP chemotherapy, although a survival benefit is yet to be determined.…”
Section: Tumor Marker Correlationmentioning
confidence: 90%